Digital Transformation and Corporate Total Factor Productivity: Empirical Evidence Based on Listed Enterprises - Guoyan Zeng; Linxing Lei (Discrete Dynamics in Nature and Society)
This paper mainly attempts to disclose the action mechanism of corporate digital transformation on total factor productivity (TFP). Based on the data on listed enterprises in 2007–2019, the influence of corporate digital transformation on TFP was analyzed empirically. The results show that corporate digital transformation can significantly promote TFP. Heterogeneity analysis reveals that the promoting effect of digital transformation on TFP only exists in small and medium high-tech enterprises, suggesting that corporate digital transform enhances TFP by improving the management efficiency and technical level of enterprises. The research provides theoretical basis and empirical evidence for improving corporate TFP from the perspective of digital transformation.